Pyrazole Carboxylic Acid and Derivatives: Synthesis and Biological Applications - Cetin, Adnan (Mini-Reviews in Organic Chemistry, 2021)
The heterocyclic compounds are the building blocks for the synthesis of the different biologically active compounds in the organic chemistry. Heterocyclic compounds have versatile synthetic applicability and biological activity. Pyrazole carboxylic acid derivatives are significant scaffold structures in heterocyclic compounds due to biologic activities such as antimicrobial, anticancer, inflammatory, antidepressant, antifungal anti-tubercular and antiviral, etc. The aim of this mini-review is an overview synthesis of pyrazole carboxylic acid derivatives and their biologic applications. The summarized literature survey presents biological activities of pyrazole carboxylic acid derivatives and their various synthetic methods in detail. This mini-review can be a guide to many scientists in medicinal chemistry.
Keywords: bioactive properties